Differences in the Arrangement of Leave Outside the State Responsibility for Presidential Candidates and Incumbent Regional Head Candidates Based on the Equality Before the Law - Muhamad Hadiyan Rasyadi (Fakultas Hukum Universitas Lampung, 2021)
The existence of differences in leave arrangements outside of the state's responsibility for incumbent candidates in the Presidential and Vice Presidential Election (pilpres) and the General Election of Regional Heads and Deputy Regional Heads (pemilukada) have an impact on the sense of justice in granting political rights attached to citizens. The research describes the arrangements' differences from the equality before the law's perspective. The type of research used is normative legal research with descriptive legal research methods. The problem approach used is statutory, comparative, and conceptual approaches. The data used in this research is secondary data, with a literature study method. Furthermore, the technique used in this research is to collect, identify and analyze the data presented in a qualitative descriptive form. The results of the research and discussion show that there are differences in leave arrangements outside of the state's responsibility for presidential and vice-presidential candidates and incumbent regional heads and deputy regional heads in the presidential and regional elections. Theoretically, every legislation formulation and application must be based on the principle of equality before as a form of social justice.